Occupational risk factors for endometriosis in a cohort of flight attendants - Candice Y Johnson; Barbara Grajewski; Christina C Lawson; Elizabeth A Whelan; Stephen J Bertke; Chih-Yu Tseng (Nordic Association of Occupational Safety and Health (NOROSH), 2016)
OBJECTIVES: This study aimed to (i) compare odds of endometriosis in a cohort of flight attendants against a comparison group of teachers and (ii) investigate occupational risk factors for endometriosis among flight attendants. METHODS: We included 1945 flight attendants and 236 teachers aged 18-45 years. Laparoscopically confirmed endometriosis was self-reported via telephone interview, and flight records were retrieved from airlines to obtain work schedules and assess exposures for flight attendants. We used proportional odds regression to estimate adjusted odds ratios (OR_adj) and 95% confidence intervals (95% CI) for associations between exposures and endometriosis, adjusting for potential confounders. RESULTS: Flight attendants and teachers were equally likely to report endometriosis (OR_adj 1.0, 95% CI 0.5-2.2). Among flight attendants, there were no clear trends between estimated cosmic radiation, circadian disruption, or ergonomic exposures and endometriosis. Greater number of flight segments (non-stop flights between two cities) per year was associated with endometriosis (OR_adj 2.2, 1.1-4.2 for highest versus lowest quartile, P trend= 0.02) but block hours (taxi plus flight time) per year was not (OR_adj 1.2, 95% CI 0.6-2.2 for highest versus lowest quartile, P trend=0.38). CONCLUSION: Flight attendants were no more likely than teachers to report endometriosis. Odds of endometriosis increased with number of flight segments flown per year. This suggests that some aspect of work scheduling is associated with increased risk of endometriosis, or endometriosis symptoms might affect how flight attendants schedule their flights.